Superconductivity, Electron Paramagnetic Resonance, and Raman Scattering Studies of Heterofullerides with Cs and Mg - V. A. Kulbachinskii; B. M. Bulychev; V. G. Kytin; A. V. Krechetov; E. A. Konstantinova; R. A. Lunin (Advances in Condensed Matter Physics)
In the present study, the results of investigation of physical properties of heterofullerides A3−xMxC60 (A=K, Rb, Cs, M=Be, Mg, Ca, Al, Fe, Tl, x=1,2); as well as RbCsTlC60, KCsTlC60, and KMg2C60 are described. All of the fullerides were synthesized by the exchange reactions of alkaline fullerides with anhydrous metal halides. Superconductivity was found in RbCsTlC60 and KCsTlC60.